DESAIN STRUKTUR SLAB ON PILE - Kurniadi, Akbar; Rosyidin, Imam Faizal; Indarto, Himawan; Atmono, Indrastono Dwi (Jurnal Karya Teknik Sipil, 2015)
Sebelimbingan – Martadipura road has a length of 2.8 km, it was built in the sub-district of Kota Bangun, Kutai Kartanegara Regency, East Kalimantan. Trace of the road must pass through areas with very soft soil condition. During the rainy season, the location of  alignment in this road flooded. To overcome these problems then built bridge using Slab on Pile structure. Slab on Pile structure consisting of slab, pile head and pile foundation. Loading standart on the structure refers to the SNI T-02-2005 (Standar Pembebanan Untuk Jembatan). Modeling of pile foundation used elastic spring reaction model, which can represent the bearing capacity of pile foundation.